Causality Relationship between Central Bank Reforms and Inflation: Evidence from Developing Countries - Cep Jandi Anwar; Okot Nicholas (Signifikan: Jurnal Ilmu Ekonomi, 2020)
This study provides evidence on the relationship between central bank reforms and inflation dynamics in a sample of 37 developing countries. We use panel structural break test and Granger non‐causality tests on annual inflation and the legal index of central bank independence (CBI), as a proxy of central bank reform, over 40 years period. The empirical results indicate a positive effect of central bank independence on inflation stabilization. Besides, we find that there exists bi-directional causality between central bank reforms and inflation. These findings suggest that central bank independence is beneficial in terms of sustained macroeconomic stabilization and should harness among developing countries. In particular, reforms should design to give central banks more autonomy in the conduct of monetary policy and financial sector regulation. JEL Classifications: E31, E58How to Cite:Anwar, C. J., & Nicholas, O. (2020). Causality Relationship Between Central Bank Reforms and Inflation: Evidence from Developing Countries. Signifikan: Jurnal Ilmu Ekonomi, Vol. 9(1), 15-30. doi: http://dx.doi.org/10.15408/sjie.v9i1.10955.